CORRELATION OF THE RESULTS OF THE EXPERIMENTS’ SERIES IN VISUALIZATION OF PAPILLAE PATTERN PRINTS AND THEIR RECOVERY FROM A DECEASED HUMAN SKIN - Zīle, Aelita (Administrative and Criminal Justice, 2019)
The phenomenon of human skin bears in the fact that in commitment of a crime it may be at the same time both a traceforming object and a trace-bearing object. Therefore, the presence of papillae pattern prints on human (victim) skin has long been of experts’ interest. Several experimental series have been conducted with the aim of finding the most optimal method for visualization and recovery of papillae pattern prints from a deceased human skin. One such experimental series was also carried out by the author of the paper.The aim of this paper is to correlate the results of experimental series. The following tasks were set to achieve the aim: to summarize the raw data and the results of the experimental series; to study and analyze common and different in raw data; to study and analyze the potential impact of differences in raw data on the outcome; to study and analyze raw data that can and cannot be influenced. The problem of the study is the divergence of views and opinions concerning the theoretical and practical aspects of the method applied. The novelty of the study is in analysis of raw data and results of experimental series, correlation of results.Analyzing the raw data of the experimental series and the results obtained by the author and foreign researchers it was stated that both similar and different raw data were used in the experimental series; there were experimental series where more raw data were used than in other experimental series; a difference was found between theoretical and practical aspects.